2016
DOI: 10.1111/bph.13385
|View full text |Cite
|
Sign up to set email alerts
|

Threonine532 phosphorylation in ClC‐3 channels is required for angiotensin II‐induced Cl current and migration in cultured vascular smooth muscle cells

Abstract: BACKGROUND AND PURPOSEAngiotensin II (AngII) induces migration and growth of vascular smooth muscle cell (VSMC), which is responsible for vascular remodelling in some cardiovascular diseases. Ang II also activates a Cl À current, but the underlying mechanism is not clear. EXPERIMENTAL APPROACHThe A10 cell line and primary cultures of VSMC from control, ClC-3 channel null mice and WT mice made hypertensive with AngII infusions were used. Techniques employed included whole-cell patch clamp, co-immunoprecipitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…CLC-3 was found to play important roles on cell volume regulation, cell migration and invasion in normal [ 18 , 19 ] and cancer cells [ 5 ]. CLC-3channels were upregulated in human glioma cell membranes [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…CLC-3 was found to play important roles on cell volume regulation, cell migration and invasion in normal [ 18 , 19 ] and cancer cells [ 5 ]. CLC-3channels were upregulated in human glioma cell membranes [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, chloride channel activity could be increased after, e.g., phosphorylation by Rho downstream signaling factors other than ROCK. Several phosphorylation sites have been identified in CLCN3 channel and its channel activity is dramatically potentiated after phosphorylation (Robinson et al, 2004 ; Cuddapah and Sontheimer, 2010 ; Ma et al, 2016 ). In addition, we have previously shown that p38/MAPK signal pathway is linked to the potentiation of TRPV1 activity by S1P (Langeslag et al, 2014 ), and in a recent report Rho can act as an upstream regulator of p38/MAPK (Shatanawi et al, 2011 ), thus p38/MAPK signaling may have a possibility of regulating the activation of Cl − current induced by S1P.…”
Section: Discussionmentioning
confidence: 99%
“…After the attainment of confluence, the VSMCs were trypsinized, and seeded onto 60 mm Petri dishes. Subconfluent VSMCs were maintained in medium devoid of serum (SMGS) for 24 h to achieve quiescence, and then stimulated by Ang II (1 μmol/L) incubation for 24 h according to previous studies [33, 34]. …”
Section: Methodsmentioning
confidence: 99%